East meets west: using ethnobotany in ethnic urban markets of Barcelona metropolitan area (Catalonia) as a tool for biocultural exchange - Ugo D'Ambrosio; Cristina Pozo; Joan Vallès; Airy Gras (BMC, 2023)
Abstract Background Ethnobotanical studies in metropolitan areas and urban ethnic markets have grown considerably in recent years as large cities have demonstrated to be significantly rich in biocultural diversity and in driving its evolution, as human populations migrate from one region to another. Urban spaces also represent important places of rich multicultural and multilingual interaction and exchange, where ethnobotany can act as a bridge between research and action. The purpose of this study is to present a case study on how to use ethnobotany in multicultural urban settings by studying people-plant interactions and the larger implications and applications to promote biocultural learning in these areas. Methods We inventoried the botanical composition of fresh and dry products sold in most food stores owned by Chinese immigrants in Fondo, a neighbourhood of Barcelona's metropolitan area, in Santa Coloma de Gramenet municipality (Barcelonès county, Catalonia, Iberian Peninsula), pharmacologically validating the obtained list with the Chinese Pharmacopoeia. We also participated in multiple dissemination activities and materials (non-academic and academic), along with exchanges with the broader community in relation to this research. Results In total, 103 plants were identified at the species level, pertaining to 88 genera and 46 botanical families. Including the infraspecific level, a total of 113 plant taxa were inventoried. One algal and six fungal species were also recorded, but not included in the analyses. Brassicaceae (12.4%) and Fabaceae (10.6%) were the most predominant families inventoried, followed by Cucurbitaceae (7.1%) and Poaceae (7.1%). Over three-quarters of all the taxa have an Asian origin (76.11%), indicating a high conservation of the use of Asian taxa. Over one-third (36.89%) of the plant parts pertain to species contained in the Chinese Pharmacopoeia, showing the relevance of medicinal plants in local stores and the preponderance of Eastern Asian food-medicine continuums. To promote ethnobotanical education programmes, over 50 dissemination activities and educational materials were produced from this study and shared with the local urban community in different fora. Conclusions Further research in these and similar settings can provide significant ethnographic information to better understand anthropological processes and phenomena underlying migration and transculturation that can be used in an umbrella of applications, from adequate nomenclature and labelling of foreign products in local languages to multicultural integration and social cohesion programmes along with educational activities on biocultural topics.